Implementing an Integrated and Communicative Approach In EFL Poetry Classroom - sutarno, sutarno (JURNAL SMART, 2018)
This study intends to describe the implementation of integrated and communicative approach to teaching poetry. Integrated and communicated approach consist three main activities; pre, while and post activities. This study employed qualitative method with case study approach. The subject of the research is the students of STKIP Muhammadiyah Pringsewu who joined poetry class. The finding shows the integrated and communicative approach could be use in teaching poem in EFL class since it is enable the students to comprehend as well as to read aloud and create of poem easier. Moreover, it is also help the students understand the text deep in conceptually and linguistically.